Comparative Genology: Genre Modifications and Genre Metamorphism - Chervinska, Olha (Zagadnienia Rodzajów Literackich, 2023)
The article under studies deals with the issue of the comparative aspects of genre. Particular emphasis has been placed on the genre form (in the sense of a characteristic matrix/canon as a complex of specific factors), which functions in terms of a continuous literary process and, accordingly, adapts to its contextual changes, deviations, objections, innovations, correlations, needs of the receptive environment. The author’s and the reader’s perception of the meanings, contained in a particular genre, do not necessarily coincide. Consequently, the issue of the so-called multiplicity of genre logic ( Jean-Marie Schaeffer’s proposal) directly appeals to the comparativistic experience of studying typological coincidences or borrowings that affect the genre as such. Fyodor Dostoevsky’s novel The Adolescent is taken as an example of genre modification. Its genre is regarded in contamination with the genre of confession by means of comparing the individual plot lines and interpreting the main characters, which are perceived in the biblical context. Besides, it acquires a different perspective in clarifying the general author’s idea. Finally, the article singles out such terminological syntagms as genre polymorphism, genre modifications, and genre metamorphism.